Developing new organisational practice: the virtual factory. (12th May 2004) - Collins, Philippa; Pluess, Adrian; Huber, Charles
Collaborative working is not new, but successful implementation of new organisational models depends on a thorough understanding of the potential of new technologies. Although there has been an explosion of e-business ventures, the implications of the internet and associated technologies for virtual working need further exploration. A practical implementation of a virtual organisation is presented to illustrate the potential of virtual working. The critical success factors, including use of technology, structural design and the human resource issues, are discussed and the benefits of this means of collaborative working are recorded. The prospects for knowledge management are illustrated, together with the management issues that must be addressed.